Implementation GStreamer framework with face detection system for Unmanned Aerial Vehicle - Yesmagambet, N.A (Bulletin of the Karaganda University. Mathematics Series, 2016)
This article provides an experimental development of unmanned aerial vehicle (UAV), and the method by which a video stream from the UAV is transmitted through the pipeline, using GStreamer framework, which in turn takes up in the ground station. Preprocessed data video link will defined the face using Viola Jones method through OpenCV library. During research was modeled drone with the flight controller based hardware computing platform "Raspberry Pi" and "Arduino" with complex algorithms based on Open Source projects "ArduQuad, Arducopter, MultiWii" on the C ++ programming language, Python. A pipe through which is passed a raw data stream videos via WiFi c UAV ground station network.